Cabozantinib in advanced non-clear-cell renal cell carcinoma: a multicentre, retrospective, cohort study. Issue 4 (April 2019) - Martínez Chanzá, Nieves; Xie, Wanling; Asim Bilen, Mehmet; Dzimitrowicz, Hannah; Burkart, Jarred; Geynisman, Daniel M; Balakrishnan, Archana; Bowman, I Alex; Jain, Rohit; Stadler, Walter; Zakharia, Yousef; Narayan, Vivek; et al.
Summary: Background: Cabozantinib is approved for patients with metastatic renal cell carcinoma on the basis of studies done in clear-cell histology. The activity of cabozantinib in patients with non-clear-cell renal cell carcinoma is poorly characterised. We sought to analyse the antitumour activity and toxicity of cabozantinib in advanced non-clear-cell renal cell carcinoma. Methods: We did a multicentre, international, retrospective cohort study of patients with metastatic non-clear-cell renal cell carcinoma treated with oral cabozantinib during any treatment line at 22 centres: 21 in the USA and one in Belgium. Eligibility required patients with histologically confirmed non-clear-cell renal cell carcinoma who received cabozantinib for metastatic disease during any treatment line roughly between 2015 and 2018. Mixed tumours with a clear-cell histology component were excluded. No other restrictive inclusion criteria were applied. Data were obtained from retrospective chart review by investigators at each institution. Demographic, surgical, pathological, and systemic therapy data were captured with uniform database templates to ensure consistent data collection. The main objectives were to estimate the proportion of patients who achieved an objective response, time to treatment failure, and overall survival after treatment. Findings: Of 112 identified patients with non-clear-cell renal cell carcinoma treated at the participating centres, 66 (59%) had papillary histology, 17 (15%) had Xp11.2 translocation histology, 15 (13%) had unclassified histology, ten (9%) had chromophobe histology, and four (4%) had collecting duct histology. The proportion of patients who achieved an objective response across all histologies was 30 (27%, 95% CI 19–36) of 112 patients. At a median follow-up of 11 months (IQR 6–18), median time to treatment failure was 6·7 months (95% CI 5·5–8·6), median progression-free survival was 7·0 months (5·7–9·0), and median overall survival was 12·0 months (9·2–17·0). The most common adverse events of any grade were fatigue (58 [52%]), and diarrhoea (38 [34%]). The most common grade 3 events were skin toxicity (rash and palmar-plantar erythrodysesthesia; five [4%]) and hypertension (four [4%]). No treatment-related deaths were observed. Across 54 patients with available next-generation sequencing data, the most frequently altered somatic genes were CDKN2A (12 [22%]) and MET (11 [20%]) with responses seen irrespective of mutational status. Interpretation: While we await results from prospective studies, this real-world study provides evidence supporting the antitumour activity and safety of cabozantinib across non-clear-cell renal cell carcinomas. Continued support of international collaborations and prospective ongoing studies targeting non-clear-cell renal cell carcinoma subtypes and specific molecular alterations are warranted to improve outcomes across these rare diseases with few evidence-based treatment options. Funding: None.